RECURRENT CHONDROMA OF THE THORACIC SPINE: A CASE REPORT - SHAHID YAKOOB; PARI.K (International Journal of Pharma and Bio Sciences, 2015)
Cartilage forming tumors are benign cartilaginous tumours that rarely affect the spinal canal. They account for 2% of all spinal tumors and 2.6 percentage of all benign tumors. A case of recurrent chondroma of thoracic spine of 25 years old female was presented with inability to walk, back pain, difficulty in passing urine and numbness of both lower limbs for one week. She had undergone total excision of chondroma of the thoracic vertebrae 3 years ago and no follow up done after surgery. MRI scan revealed, a well defined multilobulated mixed intensity, exophytic solid mass with peripheral ring like the enhancement of the capsule arising from the neural arch element of D10 vertebra with destruction of pedicle, lamina, transverse process and spinous process of D10 & D11vertebrae with extra dural extension of mass in to spinal canal with total compression of lower dorsal spinal cord and conus from D9 to D10 level. The recurrence is very rare even after subtotal removal of tumor, In summary, we present an unique case of recurrent chondroma of the thoracic spine. The early identification and surgical resection results in the prevention of malignant transformation and development of neurological deficit.